2011
DOI: 10.1007/s11104-011-0718-x
|View full text |Cite
|
Sign up to set email alerts
|

Plant-mediated CH4 transport and C gas dynamics quantified in-situ in a Phalaris arundinacea-dominant wetland

Abstract: Northern peatland methane (CH 4 ) budgets are important for global CH 4 emissions. This study aims to determine the ecosystem CH 4 budget and specifically to quantify the importance of Phalaris arundinacea by using different chamber techniques in a temperate wetland. Annually, roughly 70±35% of ecosystem CH 4 emissions were plant-mediated, but data show no evidence of significant diurnal variations related to convective gas flow regardless of season or plant growth stages. Therefore, despite a high percentage … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
27
2
2

Year Published

2013
2013
2018
2018

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 40 publications
(33 citation statements)
references
References 37 publications
2
27
2
2
Order By: Relevance
“…In contrast, Schimel (1995) found that clipping leaf blades significantly increased CH 4 flux from a Carex aquatilis site, but not from an Eriophorum angustifolium site in a wet meadow of Alaska. However, we did not find significant difference of CH 4 flux rates between shoot clipping and control treatment, which was not consistent with other studies (Ding et al 2005;Askaer et al 2011). CH 4 flux depends on the balance between CH 4 production, oxidation and transport.…”
Section: Impact Of Shoot Clipping and Root Exclusion On Ch 4 Fluxescontrasting
confidence: 99%
See 3 more Smart Citations
“…In contrast, Schimel (1995) found that clipping leaf blades significantly increased CH 4 flux from a Carex aquatilis site, but not from an Eriophorum angustifolium site in a wet meadow of Alaska. However, we did not find significant difference of CH 4 flux rates between shoot clipping and control treatment, which was not consistent with other studies (Ding et al 2005;Askaer et al 2011). CH 4 flux depends on the balance between CH 4 production, oxidation and transport.…”
Section: Impact Of Shoot Clipping and Root Exclusion On Ch 4 Fluxescontrasting
confidence: 99%
“…Previous studies have suggested that about 3 % to 4 % of net ecosystem production (NEP) is emitted back to the atmosphere as CH 4 (Whiting and Chanton 1993;Bellisario et al 1999). In this study, however, CH 4 emissions during drawdown periods were relatively low and accounted for less than 1 % of the annual carbon assimilation, which was consistent with Askaer et al (2011). This could be partly explained by a strong C sink due to the double growing season of the Carex meadow during drawdown periods (Hu et al 2015).…”
Section: Ch 4 and N 2 O Emissions During Drawdown Periodssupporting
confidence: 70%
See 2 more Smart Citations
“…It can be established from seeds as normal agricultural grass (Kandel et al, 2013b), but in some countries it is considered as an invasive species (Maurer et al, 2003). The plants thrive in wet soils due to aerenchyma tissues (Kercher and Zedler, 2004;Askaer et al, 2011) that transport oxygen to the roots in otherwise anaerobic soil compartments. However, cultivating wetland plants like RCG may influence the overall GHG balance by a combination of contrasting effects.…”
Section: Introductionmentioning
confidence: 99%